1993
DOI: 10.1159/000462403
|View full text |Cite
|
Sign up to set email alerts
|

Direct Agglutination of Weak D Red Cells by Tetramolecular Complexes Containing Monoclonal IgG Anti-D

Abstract: The capacity of blood group antibodies to agglutinate red cells suspended in saline is largely dependent on the antibody isotype. The immunological cross- linking of IgG antibodies has previously been described as a means to increase the reactivity of IgG in many situations. We have prepared anti-D-containing complexes by blending a human IgG anti-D monoclonal antibody (mAb) and a murine anti-human IgG mAb. In standard red cell serology assays, the anti-D complexes exhibited a very high avidity and could agglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Control experiments showed that the C5‐1 mAb could form agglutinating tetramolecular complexes with a human IgG anti‐D mAb (data not shown), as previously described for the 8D2‐8 murine anti‐human IgG mAb (Lemieux et al , 1993). To prepare the C5‐1/Fc tetramolecular complexes, purified C5‐1 antibodies and commercial human Fc fragments were mixed at different molar ratios and analyzed by gel filtration chromatography.…”
Section: Tetramolecular C5‐1/fc Complexessupporting
confidence: 75%
See 1 more Smart Citation
“…Control experiments showed that the C5‐1 mAb could form agglutinating tetramolecular complexes with a human IgG anti‐D mAb (data not shown), as previously described for the 8D2‐8 murine anti‐human IgG mAb (Lemieux et al , 1993). To prepare the C5‐1/Fc tetramolecular complexes, purified C5‐1 antibodies and commercial human Fc fragments were mixed at different molar ratios and analyzed by gel filtration chromatography.…”
Section: Tetramolecular C5‐1/fc Complexessupporting
confidence: 75%
“…Tetramolecular IC are cross‐shaped structures that have been shown to form spontaneously by mixing equimolar amounts of rat anti‐mouse IgG mAbs and mouse IgG (Lansdorp et al , 1986). These complexes are widely used to isolate specific cells (Thomas & Lansdorp, 1988), and we previously showed that they could be useful for transforming IgG blood group antibodies into direct agglutinating reagents (Lemieux et al , 1993). Our results showed that tetramolecular IC containing human Fc fragments and mouse anti‐human IgG, are highly potent inhibitors of anti‐D‐mediated in vitro erythrophagocytosis, and that they also inhibit the clearance of antibody‐coated platelets in a mouse model of thrombocytopenia more efficiently than IVIg.…”
mentioning
confidence: 99%